2019
DOI: 10.22146/jieb.45755
|View full text |Cite
|
Sign up to set email alerts
|

Managing Brands’ Popularity on Facebook: Post Time, Content, and Brand Communication Strategies

Abstract: Introduction: A brand’s popularity on social media affects its customers’ purchasing intention and purchasing decision. Background Problem: A review of the literature shows that a brand’s popularity on social media has a secure connection with its content and the time information about it is posted; allegedly the brand’s interactions are also influential. Indicators of its popularity include the number of likes, shares, comments, and views for it. Novelty: Previous brand popularity studies were limited to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
1
8
0
2
Order By: Relevance
“…Finally, with respect to the publication moment, the results are aligned with the findings of Hanifawati et al [59] in their work on the management of corporate Facebook accounts. In that study, the researchers emphasized that the messages in the most active time slots, those in which the user is more likely to visit the platform, increase both the amount of shared content and the comments received on it.…”
Section: Volumes Components and Publication Moments That Increase Content Recognition (Rqi)supporting
confidence: 86%
“…Finally, with respect to the publication moment, the results are aligned with the findings of Hanifawati et al [59] in their work on the management of corporate Facebook accounts. In that study, the researchers emphasized that the messages in the most active time slots, those in which the user is more likely to visit the platform, increase both the amount of shared content and the comments received on it.…”
Section: Volumes Components and Publication Moments That Increase Content Recognition (Rqi)supporting
confidence: 86%
“…Among the majority available study in this area, the study of Jahanbakhsh et al (2021) has evaluated the social media posts timing, but it mostly has concentrated on misinformation management by accurate timing of social media posts. A similar study by Hanifawati et al (2019) evaluated brands' popularity on Facebook based on post timing and content, but again, the study focused primarily on social media post timings. Very few explorations have been made in regards to page visit timing data under social media analytics in order to gain insights.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to the existing literature by Jahanbakhsh et al (2021) on the timing of social media posts, this study primarily focused on gaining insights into user activity information to gain business insights from the analytical data. This study adds to the existing research of Hanifawati et al (2019) and Wahid and Wadud (2020) to determine when is the most effective timing of user engagement on social media business pages by focusing on Great Deal Tires analytics data. With respect to the Facebook analytics data, the study agreed to the outcome of Pollard (2015) that identified highest user engagement in between 9 a.m. and 7 p.m. but also extended it by providing accurate date and time for the selected company.…”
Section: Implications Of the Studymentioning
confidence: 99%
“…Interaksi inilah yang sesungguhnya menjadi kunci untuk meningkatkan pengalaman, value, kepuasan dan niat pembelian konsumen (Alexander & Kent, 2022). Interaksi aktif antara administrator media sosial dengan konsumen dapat meningkatkan pemahaman perusahaan tentang kebutuhan konsumen yang seiring waktu terus berubah sehingga perusahaan dapat terus berinovasi mengembangkan produk dan layanan untuk memuaskan kebutuhan target pasarnya (Hanifawati, Ritonga, et al, 2019). Penggunaan media sosial oleh perusahaan memiliki dampak moderasi dalam co-creation dan menawarkan strategi segmentasi potensial (Casper Ferm & Thaichon, 2021).…”
Section: Latar Belakangunclassified